Genomic and Metagenomic Analysis of Diversity-Generating Retroelements Associated with Treponema denticola - Nimkulrat, Sutichot; Lee, Heewook; Doak, Thomas G.; Ye, Yuzhen (Frontiers in Microbiology, 2016)
Diversity-generating retroelements (DGRs) are genetic cassettes that can produce massive protein sequence variation in prokaryotes. Presumably DGRs confer selective advantages to their hosts (bacteria or viruses) by generating variants of target genes—typically resulting in target proteins with altered ligand-binding specificity—through a specialized error-prone reverse transcription process. The only extensively studied DGR system is from the Bordetella phage BPP-1, although DGRs are predicted to exist in other species. Using bioinformatics analysis, we discovered that the DGR system associated with the Treponema denticola species (a human oral-associated periopathogen) is dynamic (with gains/losses of the system found in the isolates) and diverse (with multiple types found in isolated genomes and the human microbiota). The T. denticola DGR is found in only nine of the 17 sequenced T. denticola strains. Analysis of the DGR-associated template regions and reverse transcriptase gene sequences revealed two types of DGR systems in T. denticola: the ATCC35405-type shared by seven isolates including ATCC35405; and the SP32-type shared by two isolates (SP32 and SP33), suggesting multiple DGR acquisitions. We detected additional variants of the T. denticola DGR systems in the human microbiomes, and found that the SP32-type DGR is more abundant than the ATCC35405-type in the healthy human oral microbiome, although the latter is found in more sequenced isolates. This is the first comprehensive study to characterize the DGRs associated with T. denticola in individual genomes as well as human microbiomes, demonstrating the importance of utilizing both individual genomes and metagenomes for characterizing the elements, and for analyzing their diversity and distribution in human populations.